2003
DOI: 10.1046/j.1525-1497.2003.20524.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the distal hyperplastic polyp a marker for proximal neoplasia?

Abstract: CONTEXT: The current literature is unclear about the association between distal hyperplastic polyps and synchronous neoplasia (adenomatous polyps and cancer) in the proximal colon. OBJECTIVE:To estimate the prevalence of proximal neoplasia associated with distal hyperplastic polyps.DATA SOURCES: Database searches (MEDLINE and EMBASE from 1966 to 2001) and manual search of the bibliographies of included and excluded studies, case reports, editorials, review articles, and textbooks of Gastroenterology. STUDY S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 50 publications
1
29
1
3
Order By: Relevance
“…In 2003, Dave et al [3] reviewed the literature regarding the association of distal hyperplastic polyps and synchronous neoplasia (adenomatous polyps and cancer) in the proximal colon.…”
Section: Hyperplastic Polypsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, Dave et al [3] reviewed the literature regarding the association of distal hyperplastic polyps and synchronous neoplasia (adenomatous polyps and cancer) in the proximal colon.…”
Section: Hyperplastic Polypsmentioning
confidence: 99%
“…Of 18 included studies, 12 involved asymptomatic individuals in which the pooled absolute risk of any proximal neoplasia associated with distal hyperplastic polyps was 25% [3]. In 4 studies where colonoscopy was performed irrespective of distal findings, the absolute risk was 21% (95% confidence interval (CI), 14-28%).…”
Section: Hyperplastic Polypsmentioning
confidence: 99%
“…To date, 13 trials have been conducted on the proposed topic and target population. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although the authors of seven [5][6][7][8][9][10][11] of these studies have concluded that distal HPs do predict the presence of SPNs and necessitate colonoscopy, the authors of the remaining six [12][13][14][15][16][17] have reported that no such increased risk exists, thus nullifying the need for colonoscopy. Moreover, beyond these visible discrepancies within the published literature, there are also tangible inconsistencies among the formal recommendations made for patients with distal HPs discovered by screening FS.…”
Section: Risk Of Proximal Colonic Neoplasms In Asymptomatic Adults Olmentioning
confidence: 99%
“…18,19 In contrast, the American Cancer Society, the Agency for Health Care Policy and Research, and the US Preventive Services Task Force believe that there is not enough substantial evidence to make a sound recommendation either way; therefore, these organizations have offered no explicit suggestions for this subgroup of patients. 4 This unfortunately has culminated in an enduring and persisting knowledge gap. Consequently, many physicians and clinicians currently do not order any additional testing when HPs are the only significant finding on an FS.…”
Section: Risk Of Proximal Colonic Neoplasms In Asymptomatic Adults Olmentioning
confidence: 99%
“…In many studies, the main focus was on the association between distal HPs and synchronous, proximal, advanced adenomas because of colorectal cancer (CRC) screening practices [8,9,10,11,12,13]; however, the results of these studies are conflicting. Some studies have shown that the risk of proximal advanced adenomas was increased in patients with distal HPs [9,12].…”
Section: Introductionmentioning
confidence: 99%